PENGARUH PROMOSI INSTAGRAM @SSCHILDSIDOARJO TERHADAP MINAT MENJADI RELAWAN PADA PROGRAM KELAS MERDEKA SAVE STREET CHILD SIDOARJO: (Studi Pada Relawan Komunitas Save Street Child Sidoarjo) - Maudia, Laurita; Sukardani, Puspita (The Commercium, 2024)
Promotion is not only relevant to for-profit companies or organizations, but also essential for a community or non-profit organization. The presence of the Save Street Child Sidoarjo community is a response to the social issue of street children in Sidoarjo, particularly in the field of education. This community has carried out a series of promotional efforts aimed at increasing volunteer interest as educators in the Kelas Merdeka program run through the Instagram account @sschildsdioarjo. This study aims to determine the influence of Instagram promotion @sschildsidoarjo on interest in becoming volunteers in the Free Class program of Save Street Child Sidoarjo. The research is a correlational quantitative study with a simple linear regression method. The results of this study indicate that Instagram promotion has a positive and significant influence on the dependent variable, Interest. This means that the better the promotion conducted through Instagram @sschildisodarjo, the more it will increase someone's interest in becoming a volunteer in the Kelas Merdeka program of Save Street Child Sidoarjo. The high percentage of influence at 59.2% indicates that the Instagram promotion efforts @sschildsidoarjo have successfully created a significant impact in increasing individuals' interest in participating as volunteers in the Kelas Merdeka program.